Correlates of Histologic Activity and Chronicity Indices in Adult Patients with Glomerulonephritides: A Nigerian Picture - Bamikefa, T A; Adelakun, A; Adefidipe, A; Omosule, B; Ezeugonwa, R; Omotoso, B; Hassan, M O; Okunola, O O; Sanusi, A A; Arogundade, F A (West African journal of medicine, 2025)
Globally, glomerulonephritis with its diverse clinical manifestations and histologic attributes still maintains a dominant position among the myriads of aetiological culprits associated with the pathophysiologic course of chronic kidney disease. This study distinctively correlated the graded and scored histologic features observed in the glomerulus and tubulo-interstitium with clinical and biochemical features. A hospital-based cross-sectional study of 70 adult patients who presented consecutively with features of glomerulonephritis was carried out. Renal biopsies were undertaken after renal function assessment. Light microscopy and immunoperoxidase staining utilising IgA, IgM, IgG and C3 antibodies were carried out on the biopsied renal tissues. The degree of glomerular, tubular, interstitial and vascular affectation were graded and scored. Total activity and chronicity indices were collated and their association/correlation with clinical parameters assessed. Male gender predominated (67.2%) with an overall mean age of 28.4 ±10.3 years. Statistically significant correlations were found between interstitial oedema with serum creatinine (r=0.35, p=0.003) and GFR (r=-0.38, p=0.004); interstitial infiltrate with serum creatinine (r=0.52, p<0.0002) and GFR (r=-0.70, p=0.002); total activity index with serum creatinine (r=0.60, p=0.0001) and GFR (r= -0.48, p = 0.004). Statistically significant correlations were also seen between total chronicity indices with serum creatinine (r=0.62, p=0.001) and GFR (r= -0.58, p<0.001). Both activity and chronicity indices significantly influenced renal function. The higher they are, the lower the GFR and vice versa. These further buttress the need for aggressive management protocol for GN patients with higher indices to slow down renal function decline.